Transformational Leadership and Auditor Performance: A Bibliometric Study - Iqbal, Mohamad; Winarningsih, Srihadi; Mubarrok, Ahmad Zakie (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
This study aims to examine global research trends on transformational leadership and auditor performance, with a focus on identifying dominant themes, intellectual structures, and research gaps using a bibliometric approach. A total of 1,547 documents published between 2015 and 2025 were retrieved from the Scopus database. After applying defined inclusion and exclusion criteria, 524 relevant articles were selected for analysis. VOSviewer version 1.6.20 was used to perform keyword co-occurrence mapping, cluster analysis, and overlay visualization to detect thematic structures and temporal developments in the field. The analysis revealed three major thematic clusters: (1) transformational leadership behavior and organizational adaptability, (2) psychological dimensions including motivation and professional skepticism, and (3) audit performance evaluation and empirical methods. Research activity has increased consistently, with a growing emphasis on applied and sector-specific leadership studies. Contributions were concentrated in countries such as the United States, Germany, and China, while studies from developing regions and public sector contexts were notably limited. This study provides a comprehensive overview of the evolving research on transformational leadership in auditing. It highlights the dominance of Global North scholarship and the lack of public sector focus as key gaps. Future research should expand contextual diversity, incorporate emerging behavioral constructs, and explore the role of leadership in enhancing public audit performance and accountability.  Keywords: Transformational leadership; auditor performance; auditing research.